1989
DOI: 10.1007/bf01788024
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward mental illness: Recognition, desired social distance, expected burden and negative influence on mental health among Turkish freshmen

Abstract: Attitudes toward three types of disorders and a normal subject portrayed in vignettes were assessed among university students. The variables assessed were: perception of mental illness in the vignettes; desired social distance; emotional and physical burden expected; and expected negative influence on one's mental health from association with the type of persons portrayed in the vignettes. Analysis revealed that, in terms of variables assessed, the most "negative" ratings were recorded for the paranoid schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 13 publications
(14 reference statements)
2
24
1
3
Order By: Relevance
“…Previous studies on the attitudes of lay people about mental illness in Turkey have focused mainly on the recognition and detection of mental illness (Eker, 1989;Eskin, 1989), and effects of social contact with the mentally ill (Arkar & Eker, 1997;Çirakoglu, 1999). Being informed about lay theories of Turkish people will help professionals to utilize effective strategies in treatment of depression and developing programs.…”
mentioning
confidence: 99%
“…Previous studies on the attitudes of lay people about mental illness in Turkey have focused mainly on the recognition and detection of mental illness (Eker, 1989;Eskin, 1989), and effects of social contact with the mentally ill (Arkar & Eker, 1997;Çirakoglu, 1999). Being informed about lay theories of Turkish people will help professionals to utilize effective strategies in treatment of depression and developing programs.…”
mentioning
confidence: 99%
“…One of the first research papers on the topic was written in 1989 by Eker, who explored the attitudes of first-year students in Turkey towards different types of mental disorders (8). The results showed that the most negative scores were found in reports of opinions about paranoid schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, however, have been conducted in different regions and social settings in Turkey. For example, according to Eker (1989) and Eker and Arkar's (1994) study amongst the Turkish participants paranoid schizophrenia was the most recognized but the least accepted mental health problem. Arkar and Eker (1994) also found that people are more willing to distance themselves with a person who is diagnosed with paranoid schizophrenia as opposed to someone with a diagnosis of withdrawn schizophrenia or major depression.…”
Section: Introductionmentioning
confidence: 99%